The activity of a PI3K δ-sparing inhibitor, MEN1611, in non-small cell lung cancer cells with constitutive activation of the PI3K/AKT/mTOR pathway - Papoff, Giuliana; Presutti, Dario; Fustaino, Valentina; Parente, Andrea; Calandriello, Clelia; Alemà, Stefano; Scavizzi, Ferdinando; Raspa, Marcello; Merlino, Giuseppe; Salerno, Massimiliano; Bigioni, Mario; Binaschi, Monica; et al. (Frontiers in Oncology, 2023)
Background Lung cancer remains the leading cause of cancer-related death worldwide. Targeted therapies with tyrosine kinase inhibitors (TKIs) result in improvement in survival for non-small cell lung cancer (NSCLC) with activating mutations of the epidermal growth factor receptor (EGFR). Unfortunately, most patients who initially respond to EGFR-TKI ultimately develop resistance to therapy, resulting in cancer progression and relapse. Combination therapy is today a common strategy for the treatment of tumors to increase the success rate, improve the outcome and survival of patients, and avoid the selection of resistant cancer cells through the activation of compensatory pathways. In NSCLC, the phosphoinositide-3-kinase/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) pathway has been heavily implicated in both tumorigenesis and the progression of disease. Objectives In this study, we investigated the efficacy of a PI3K δ-sparing inhibitor, MEN1611, in models of NSCLC sensitive and resistant to EGFR inhibitors (erlotinib and gefitinib) with a wild-type PIK3CA gene. Methods We performed functional, biochemical, and immunohistochemistry studies. Results We demonstrated good efficacy of MEN1611 in NSCLC devoid of PIK3CA gene mutations but with constitutive activation of the PI3K/AKT pathway and its synergistic effect with gefitinib both in vitro and in vivo. Conclusions Overall, this preclinical study indicates that the inhibitor could be a candidate for the treatment of NSCLC with an erlotinib/gefitinib-resistant phenotype and constitutive activation of the PI3K/AKT pathway, a phenotype mimicked by our model system.